Editorial - Barboza Jiménez, Lucrecia (2010)
We give a warm welcome to a new issue of the Library. This edition brings together a number (as) author (s) that enrich their new contributions to the discipline and contribute to the upgrading and continuing education and professional work daily with the information and library education.